Proportion and Outcome of Induction of Labor Among Mothers Who Delivered in Teaching Hospital, Southwest Ethiopia - Yosef, Tewodros; Getachew, Dawit (Frontiers in Public Health, 2021)
Background: Despite the induction of labor had some unwanted consequences, it has also several benefits for maternal and perinatal outcomes. Induction of labor is done when the benefits of delivery out-weight the risk of continuing the pregnancy. This study aimed to assess the prevalence, outcome, and consequences of induction of labor among mothers who delivered at Mizan-Tepi University Teaching Hospital in southwest Ethiopia. Methods: A cross-sectional study was conducted among women’s who delivered from November 30, 2018 to May 30, 2019 in Mizan-Tepi University Teaching hospital. From a total of 1760 mothers who delivered in the above specified period, 294 mother cards were reviewed using a structured checklist from June 10 to June 20, 2019 to assess the prevalence, outcome, and consequences of induction of labor. A binary logistic regression analysis was computed. Significance was declared at p < 0.05 in the multivariable logistic regression analysis. Results: Of the 294 cards reviewed, the prevalence of induction of labor was 20.4%. The commonest reason for induction was preeclampsia (41.6%). The factors associated with induction of labor were mothers aged 25-34 years (AOR = 2.55, 95% CI [1.18-5.50]) and ≥ 35 years (AOR = 10.6, 95% CI [4.20-26.9]), having no history of antenatal care (AOR = 2.12, 95% CI [1.10-4.07]) and being primipara (AOR = 2.33, 95% CI [1.18-3.24]). Of the 60 induced mothers, 23.3% had failed induction. The proportion of mothers with dead fetal outcomes and maternal complications were 5% and 41.7% respectively. The study also revealed that unfavorable Bishop score before induction (AOR = 9.15, 95% CI [1.52-55.2]) and induction using misoprostol (AOR = 4.72, 95% CI [1.07-20.9]) were the factors associated with failed induction of labor. Conclusion: The prevalence of induced labor was much higher than rates in other Ethiopian studies; however, the prevalence of failed induction was comparable to other studies done in Ethiopia. The study revealed that unfavorable Bishop score before induction and induction using misoprostol were the factors associated with failed induction. Therefore, the institution should revise the induction guideline to increase the success rate of induction of labor.